Impact of harvesting seasons on physicochemical properties and volatile compound profiles of Malaysian stingless bee honey analysed using chemometrics and support vector machine - Sharin, Siti Nurhidayah; Abdullah Sani, Muhamad Shirwan; Kassim, Nur Kartinee; Yuswan, Mohd Hafis; Abd Aziz, Azharuddin; Jaafar, Mohd Azwan; Hashim, Amalia Mohd (Elsevier, 2024)
Stingless bee honey's nutritional value is gaining attention, but the impact of harvesting seasons, specifically the rainy (September 2018) and dry (February 2019) seasons in Malaysia on the honey's physicochemical properties and volatile compounds remains insufficiently explored. This research revealed marginal differences in the physicochemical properties between seasons. However, through individual bee species and cumulative data analysis, honey samples were effectively differentiated based on harvesting seasons. A set of seventeen volatile compounds were identified as potential chemical markers for distinguishing H. bakeri, G. thoracica, and T. binghami honey between rainy and dry seasons. For cumulative data, four significant markers were proposed. These discrimination methods and chemical markers can serve as valuable references in distinguishing stingless bee honey, whether its entomological origin is specified or not between rainy and dry seasons.